Case Report: Primary leiomyosarcoma of the canine gallbladder with intraoperative indocyanine green near-infrared fluorescence imaging - Yun, Jongchul; Kim, Yujin; Park, Kyung-Mee; Lee, Sungin (Frontiers in Veterinary Science, 2025)
A 13-year-old castrated male, Maltese was presented for abnormal findings of gallbladder on abdominal ultrasonography without clinical signs. Abdominal ultrasonography revealed a severely distended gallbladder and a heterogeneous echogenic mass in the gallbladder neck. No evidence of metastasis was observed. Cholecystectomy was performed with indocyanine green near-infrared fluorescence imaging for real-time visualization of the biliary tract that contributed to improve surgical outcomes. In the histopathological examination and immunohistochemical analysis using smooth muscle actin staining, the gallbladder mass was confirmed as a leiomyosarcoma. The patient has been followed up for 18 months without any signs of recurrence or metastasis. This is the first reported case of gallbladder leiomyosarcoma in dogs. Leiomyosarcoma should be considered a differential diagnosis for dogs with gallbladder mass. The histologic low grading, the absence of microscopic residual tumor and metastasis relate to good prognosis.